Front Cover: Photoacoustic imaging of the human placental vasculature (J. Biophotonics 4/2020). Issue 4 (24th April 2020) - Maneas, Efthymios; Aughwane, Rosalind; Huynh, Nam; Xia, Wenfeng; Ansari, Rehman; Kuniyil Ajith Singh, Mithun; Hutchinson, J. Ciaran; Sebire, Neil J.; Arthurs, Owen J.; Deprest, Jan; Ourselin, Sebastien; Beard, Paul C.; et al.
Abstract: Successful therapy of twin‐to‐twin transfusion syndrome requires accurate imaging to guide laser photocoagulation of the anastomosing placental vessels. Photoacoustic (PA) imaging is an alternative imaging method that provides contrast for hemoglobin, and in this study, it was used to visualize chorionic superficial and subsurface vasculature in human placentas. The strong potential of PA imaging to guide minimally invasive fetal therapies was demonstrated. Further details can be found in the article by Efthymios Maneas, Rosalind Aughwane, Nam Huynh, et al. (e201900167 ). Abstract : Successful therapy of twin‐to‐twin transfusion syndrome requires accurate imaging to guide laser photocoagulation of the anastomosing placental vessels. Photoacoustic (PA) imaging is an alternative imaging method that provides contrast for hemoglobin, and in this study, it was used to visualize chorionic superficial and subsurface vasculature in human placentas. The strong potential of PA imaging to guide minimally invasive fetal therapies was demonstrated. Further details can be found in the article by Efthymios Maneas, Rosalind Aughwane, Nam Huynh, et al. (e201900167 ).